Cerium doped Zr-based metal-organic framework as catalyst for direct synthesis of dimethyl carbonate from CO2 and methanol. (February 2023) - Huo, Linmeng; Wang, Lin; Li, Jingjie; Pu, Yanfeng; Xuan, Keng; Qiao, Congzhen; Yang, Hao
Abstract: The disadvantage of Ce/Zr metal oxide as catalyst for direct synthesis dimethyl carbonate (DMC) from CO2 and methanol is low DMC formation rate because of its low specific surface area and active sites. In this work, it can be improved by highly uniform dispersion cerium doped Zr-based metal-organic frameworks (UiO-66 MOFs), which were synthesized via a modified hydrothermal method. The as-prepared catalysts have been extensively characterized using XRD, BET, FT-IR, SEM, TEM, TGA, NH3 -TPD, CO2 -TPD, XPS techniques. Experimental evaluation results indicated that the highly uniform dispersed Ce-doped UiO-66 MOFs exhibited markedly improved catalytic performance than traditional Ce/Zr metal oxide catalyst. The highest yield of DMC catalyzed by Ce-UiO-66–2 was 0.295% (reaction time was 12 h; reaction temperature was 140 °C; reaction pressure was 11 MPa). Then, it was found that doping of Ce atoms into the zirconium lattice to produce UiO-66 MOFs could effectively increase the number of acidic and medium basic sites than UiO-66 (none Ce), thus could greatly enhance the catalytic performance. Moreover, using 2-cyanopyridine as dehydrating agent, the DMC yield could be further raised greatly. Last, based on reported literature and our results, a possible reaction mechanism over Ce-UiO-66-X was proposed. Graphical Abstract: ga1 Highlights: Ce-doped UiO-66 material (Ce-UiO-66-X) was prepared by one-step synthesis. Ce modification increased the number of acid-base active sites and specific surface area. Both acid-medium base sites and specific surface area promoted DMC formation. DMC yield can be increased by about ten times in presence of 2-cyanopyridine.